High serum Antimullerian hormone levels are associated with lower live birth rates in women with polycystic ovarian syndrome undergoing assisted reproductive technology - Reshef Tal; Charles M. Seifer; Moisey Khanimov; David B. Seifer; Oded Tal (BMC, 2020)
Abstract Introduction Antimullerian hormone (AMH) strongly correlates with ovarian reserve and response to controlled ovarian stimulation. Emerging data suggests that serum AMH level may also predict ART outcomes. However, AMH is characteristically elevated in PCOS women and it is unknown whether it may predict live birth outcomes in this population. Methods This was a retrospective cohort study of 184 PCOS women (Rotterdam criteria) who underwent their first fresh IVF/ICSI cycle. Women were divided into 3 groups according to the <25th (low), 25 to 75th (average), or > 75th (high) percentile of serum AMH concentration. Cycle stimulation parameters and reproductive outcomes were compared between groups. Results Women in the low serum AMH group were older than those in the average or high AMH (p < 0.05), and required greater gonadotropin dose for stimulation compared to the high AMH group (p < 0.05). Women with high AMH had greater testosterone level compared to women in the low or average AMH groups. No differences were noted between groups in terms of maximal E2, oocytes retrieved and fertilization rate. However, low serum AMH women had significantly greater live birth rates (p < 0.05) and showed a trend towards greater clinical pregnancy rates compared to women in the average and high AMH groups (p = 0.09). The significant association of AMH with live birth rate remained after adjusting for age, BMI, day of transfer and number of embryos transferred. Conclusions In PCOS women, elevated AMH concentrations are associated with hyperandrogenism and lower live birth rates.